2015
DOI: 10.1111/famp.12146
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Evaluation and Initial Adaptation of a Parent Training Program for Hispanic Families of Children with Autism

Abstract: The present paper takes a translational approach in applying the themes of the current special section to prevention and intervention science in Latino families. The paper reviews the current literature on cultural processes in prevention and intervention research with Latino families. Overall, many prevention and intervention programs have either been developed specifically for Latino families or have been modified for Latino families with great attention paid to the socio-cultural needs of these families. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 56 publications
0
26
0
1
Order By: Relevance
“…We were therefore surprised at the prominent role that Latino identity and culture, even over the child’s disability, played in our qualitative findings. This finding has important implications for future research as well as intervention programs, namely that focusing on children with ASD as a whole may not be sufficient; rather, culturally-informed oral care interventions are critical for addressing Latino families’ needs [73,74,75]. Indeed, recent research has shown that employing a tailored approach to conducting interventions for Latino families that incorporates Latino cultural components are successful [76].…”
Section: Discussionmentioning
confidence: 99%
“…We were therefore surprised at the prominent role that Latino identity and culture, even over the child’s disability, played in our qualitative findings. This finding has important implications for future research as well as intervention programs, namely that focusing on children with ASD as a whole may not be sufficient; rather, culturally-informed oral care interventions are critical for addressing Latino families’ needs [73,74,75]. Indeed, recent research has shown that employing a tailored approach to conducting interventions for Latino families that incorporates Latino cultural components are successful [76].…”
Section: Discussionmentioning
confidence: 99%
“…However, most early intervention research is carried out with White, mid to upper-class, monolingual English-speaking samples (Baranek et al, 2015; Roberts & Kaiser, 2011; Rogers et al, 2012; Wetherby et al, 2014). Unfortunately, research-based ASD interventions designed for and tested with White, mid to upper-class, monolingual English-speaking children may not be as effective for groups differing in language or culture, including Latino families and children (Buzhardt, Rusinko, Heitzman-Powell, Trevino-Maack, & Mcgrath, 2015; Elder, Valcante, Won, & Zylis, 2003; Zayas & Rojas-Flores, 2002). Providing diverse families of children with ASD with the most effective and culturally appropriate services requires adaptations to current evidenced-based interventions or the creation of new interventions.…”
mentioning
confidence: 99%
“…Other authors have already stressed the need to extend the intervention period to find evidence of effectiveness and impact. Some other improvements should also be considered in order to achieve a better cultural and linguistic adaptation to participants' profile and their context, as suggested for other parental programs addressing specific populations with specific needs (Buzhardt, Rusinko, Heitzman-Powell, Trevino-Maack, & McGrath, 2015;Domenech Rodriguez, Baumann, & Schwartz, 2011).…”
Section: Implications and Future Directionsmentioning
confidence: 99%